Penggunaan Agregat Sungai Radda Kecamatan Masamba Kabupaten Luwu Utara Sebagai Campuran Beton - Yenni Sri Agesya Kapuangan; Mara, Junus; Jujun Sanggaria, Olan (Paulus Civil Engineering Journal, 2025)
The Radda River has aggregates with non-uniform grain distribution, clean, and visually seen with clear river flow. However, it is not yet known whether the Radda River aggregate can be used as structural concrete. This study was conducted to determine the compressive strength, flexural strength, splitting tensile strength of concrete and modulus of elasticity of concrete using aggregates from the Radda River. This study used the SNI 7656-2012 concrete design method with concrete quality f'c 25 MPa and 32 MPa through slump test on 28-day-old concrete. The average splitting tensile strength value of f'c 25 MPa concrete is 3.017 MPa. The average splitting tensile strength value of f'c 27 MPa concrete. The average flexural strength of f'c 25 MPa concrete is 3.759 MPa. The average flexural strength of f'c 32 MPa concrete is 4.176MPa. The results of the elastic modulus test for quality f'c 25 Mpa are 18,713.811 MPa. Theoretical value = 4700 x √25 = 23,500 MPa. The results of the elastic modulus test for quality f'c 32 Mpa are 27673.21667 Mpa. Aggregates from the Radda River can be used to achieve a quality of 25 MPa and 27 MPa using a material composition of 32 MPa.